Transformational Leadership Style Of Kiai In Improving Student Character Education - Buhori, Agus; Sujiarto, Heru; Nurjaman, Ujang; Khori, Ahmad (International Journal of Educational Research & Social Sciences, 2022)
This research is motivated by a description of the conditions in the field, the still weak leadership of pesantren in improving the character of santri in Sukabumi district. So that the focus of the problem in this research is directed at the kiyai's transformational leadership in improving the character of the santri. Various problems of transformational leadership style in improving the character of the santri depend on the leadership of the kiyai, if the kiyai in leading well using transformational leadership will have a positive impact on the character of the santri in the Assalam Islamic boarding school and the Assalafiyah Islamic boarding school, but on the contrary if the kiyai's transformational leadership is not good at leading the students, the character santri do not meet the expected standard. This study aims to analyze and find empirically about the kiyai's transformational leadership style in improving the character of santri in Islamic boarding schools Assalam and Islamic boarding schools Assalafiyah. The research process was carried out through the identification of phenomena that occurred in the leadership style of telling the kiyai's to improve the character of the santri, the selling leadership style of the kiyai's in improving the character of the santri, the leadership of the participating kiyai's in improving the character of the santri, the leadership style of delegating the kiyai's in improving the character of the santri, the obstacles faced by the style of transformational leadership in improving the character of students. The methods used for data collection are analytical descriptive methods and qualitative approaches with data collection techniques based on observations, interviews and data documentation from respondents. The results of this study are. 1. The telling leadership style is applied by kiyai's in improving the character education of students in Java. West especially in Assalam Islamic Boarding School and Assalafiyah Islamic Boarding School, because there are still many subordinates (asaatidz and stakeholders) who have not been able to interpret the goals of the pesantren in terms of tasks and performance. inability of subordinates seen in carrying out tasks without direction, and not confident. 2. The selling leadership style, the kiyai's attitude in relationship behavior seems to shift to be more pro-active in motivating and appreciating subordinates. Thus, the leader shows a lot of directing behavior and provides a lot of support. 3. Participating leadership style encourages followers to participate in two-way communication, and facilitates followers in decision making. Participating leadership style is proven to be applied by kiyai's. 4. The style of delegating (delegating) is applied when the maturity level of the subordinate is high because he is able and willing or confident in assuming responsibility, this style is chosen and applied by the kiyai's in improving the character education of santri in Islamic boarding schools in Assalam Islamic Boarding Schools and Assalafiyah Islamic Boarding Schools 5. Stylistic constraints transformational leadership in improving character education, namely in relationship behavior related to the attitudes and actions of subordinates personally and in groups in responding to work, such as employees having a smarter sense.